Although Coronary Mortality Has Decreased, Rates of Cardiovascular Disease Remain High: 21 Years of Follow‐Up Comparing Cohorts of Men Born in 1913 With Men Born in 1943. Issue 9 (13 September 0207) - Fu, Michael; Rosengren, Annika; Thunström, Erik; Mandalenakis, Zacharias; Welin, Lennart; Caidahl, Kenneth; Pivodic, Aldina; Zhong, You; Ergatoudes, Constantinos; Morales, David; Welin, Catharina; Svärdsudd, Kurt; et al.
Abstract : Background: Despite a decline in mortality rates from cardiovascular disease (CVD) in the past few decades, the burden of CVD in a contemporary population remains inadequately addressed. Therefore, this study was aimed to investigate secular trends in mortality from coronary artery disease and all‐cause mortality over 2 decades, by comparing 2 cohorts of men born 30 years apart and evaluate the prediction of the risk of CVD and all‐cause death in a contemporary random sample of Swedish men. Methods and Results: Two cohorts of randomly selected men born in 1913 (855 men) and 1943 (798 men) were first examined at age 50 in 1963 and 1993, respectively, and followed longitudinally over 21 years. All‐cause mortality and coronary artery disease death were lower in 50‐ to 71‐year‐old men born in 1943 compared with those born in 1913, with unadjusted hazard ratios of 0.57 (0.45–0.71) and 0.34 (0.22–0.53), respectively. After adjustment for risk factors (smoking, serum cholesterol, hypertension, systolic blood pressure, diabetes mellitus, body mass index, and physical activity), the differences between the cohorts remained significant for coronary artery disease, hazard ratios 0.57 (0.34–0.94), P =0.029, but not for all‐cause mortality hazard ratios 0.82 (0.62–1.07), P =0.14. However, the rate of CVD events during follow‐up was still high (30.7%) for the men born in 1943. No statistically significant interaction by birth cohort in contribution of risk factors to death was found between 2 cohorts except physical inactivity. Conclusions: Despite a marked reduction in the rate of coronary artery disease death over the past 30 years, the burden of CVD events and all‐cause mortality remains high. Therefore, intensified efforts to modify contributing risk factors are still required.